Environmental and Material Flow Cost Accounting - Jasch, Christine M. (Springer, 2017)
Recognizing the increasing importance of environmental issues, energy prices, material availability and efficiency and the difficulty of adequately managing these issues in traditional accounting systems, several companies all over the world have started implementing Environmental and Material Flow Cost Accounting (EMA and MFCA). "Environmental and Material Flow Costs Accounting" explains and updates the approach developed for the United Nations Department of Economic and Social Affairs (DSD/UNDESA) and the International Federation of Accountants (IFAC) and in addition includes experiences of several case studies and recent developments regarding EMA and MFCA in national statistics and ISO standardization. Although it is aimed primarily at professional accountants, process technicians and environmental managers within production companies, it will also be of interest to environmental auditors who are becoming more involved in tracking or verifying environment-related information in financial and other relevant reports. Those involved with environmental management and cleaner technologies, production planning and organization, as well as management accounting and sustainability reporting will undoubtedly find this Work to be an invaluable guide in acquiring practical advice.